Overwinter Phenology of Plants in a Polar Semi-desert - Bell, Katherine L.; Bliss, L.C. (ARCTIC, 1977)
Arctic and temperate-latitude tundra plants must make efficient use of the growing season, because it is very short. A variety of leaf-development strategies permit growth in the cool summers. . Winter phenology was observed under field conditions for 27 of 33 angiosperm species found on King Christian Island. . The full significance of overwintering leaf condition and the variability of this pattern within the High Arctic needs further investigation.